DEMOKRASI EKONOMI ANTARA KEBERANIAN DAN BAYANGAN KEGAGALAN - Damianus J. Hali (Bina Ekonomi, 2001)
Economic democracy concept is really special for Indonesia. It is not too many States to apply that terminology in their economic activities. Of course, that Moh. Hatta's opinion has a reason: Nevertheless in fact today, economic democracy ( Demokrasi Pancasila ) has to fight in powerful of current in Middle globalization and pressure international economic regim. If we have seen Basic of economic democracy concept which is "Religious socialism" that is Very crumbly and not customary. Because of that, to go by this article I will tom Ask question and doubtful about Indonesia economic concept. I think, Hatta's Economic concept has experience hard examination today and be shadow by total failure.